Microgravity studies of solidification patterns in model transparent alloys onboard the international space station - ŞEREFOĞLU KAYA, MELİS (My University, 2023)
We review recent in situ solidification experiments using nonfaceted model transparent alloys in science-in-microgravity facilities onboard the International Space Station (ISS), namely the Transparent Alloys (TA) apparatus and the Directional Solidification Insert of the DEvice for the study of Critical Liquids and Crystallization (DECLIC-DSI). These directional-solidification devices use innovative optical videomicroscopy imaging techniques to observe the spatiotemporal dynamics of solidification patterns in real time in large samples. In contrast to laboratory conditions on ground, microgravity guarantees the absence or a reduction of convective motion in the liquid, thus ensuring a purely diffusion-controlled growth of the crystalline solid(s). This makes it possible to perform a direct theoretical analysis of the formation process of solidification microstructures with comparisons to quantitative numerical simulations. Important questions that concern multiphase growth patterns in eutectic and peritectic alloys on the one hand and single-phased, cellular and dendritic structures on the other hand have been addressed, and unprecedented results have been obtained. Complex self-organizing phenomena during steady-state and transient coupled growth in eutectics and peritectics, interfacial-anisotropy effects in cellular arrays, and promising insights into the columnar-to-equiaxed transition are highlighted.
Keywords: Tıp; Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Biyoteknoloji ve Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Fizik; Astronomi ve Astrofizik; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Medicine; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; Biotechnology and Genetics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Physics; Astronomy and Astrophysics; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Tarım Bilimleri; Klinik Tıp; Malzeme Bilimi; Uzay bilimi; TARIM, MULTİDİSİPLİNLER; MALZEME BİLİMİ, BİYOMATERYAL; TIP, GENEL & DAHİLİ; ASTRONOMİ VE ASTROFİZİK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); AGRICULTURAL SCIENCES; CLINICAL MEDICINE; MATERIALS SCIENCE; SPACE SCIENCE; MOLECULAR BIOLOGY & GENETICS; AGRICULTURE, MULTIDISCIPLINARY; MATERIALS SCIENCE, BIOMATERIALS; MEDICINE, GENERAL & INTERNAL; ASTRONOMY & ASTROPHYSICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Tıp (çeşitli); Malzeme Bilimi (çeşitli); Fizik Bilimleri; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Tarım ve Biyoloji Bilimleri (çeşitli); Fizik ve Astronomi (çeşitli); Uzay ve Gezegen Bilimi; Medicine (miscellaneous); Materials Science (miscellaneous); Physical Sciences; Biochemistry, Genetics and Molecular Biology (miscellaneous); Agricultural and Biological Sciences (miscellaneous); Physics and Astronomy (miscellaneous); Space and Planetary Science